Imagination and Empathy in Relation to the Past. Krzysztof Zamorski’s Work with the Historiographical Narrative Form and the Context of Józef Ignacy Kraszewski’s “Documentary Novel” - Julkowska, Violetta (Sensus Historiae, 2025)
The text of the article refers to the latest book by Krzysztof Zamorski, Pleban i wieś. Historia życia proboszcza tenczyńskiego z początków XVIII wieku. Studium mikrohistoryczne [The Plebanus and the Village. A Life History of the Parish Priest of Tenczynek in the Early Eighteenth Century: A Microhistorical Study], published in the “Historia życia” series by Universitas in Kraków (2025). The article is written from the perspective of the history of historiography and studies on historical narration. Firstly, this dual perspective focuses the analysis and interpretation of Zamorski’s book on the problem of exploiting the potential of historical sources in order to create an image of the past reality from a microhistorical perspective. In Zamorski’s narrative, the image of the past is constructed with meticulous care, commitment, and a sensitive understanding of the source material, as befits the art of historical interpretation and narration. Secondly, the perspective of constructing historical narration draws attention to the artistic devices that the Author skillfully employs when bringing the everyday life of Tenczynek closer to the reader, especially in the aspect of the dramatic and tragic dimension of the plague. The author’s proficient handling of sources suggests a comparison with another master of historical narration, J. I. Kraszewski, and his methods of preparing historical narrative based solely on historical sources in the form of a “documentary novel.” Zamorski “listens attentively” to the testimony of the sources and constructs an exceptionally empathetic representation of the past.